Testosterone and imipramine have antidepressant effects in socially isolated male but not female rats - Carrier, Nicole (2012)
RATIONALE: Affective disorders are twice as likely to occur in women as they are in men suggesting a critical role for gonadal hormones in their etiology. In particular, testosterone has been shown to have protective effects in men. OBJECTIVE: To investigate antidepressant effects and interactions between testosterone and imipramine in socially isolated male and female rats. METHODS: A chronic social isolation model was used to induce an anxiety and depressive-like state in adult gonadectomized (Gnx) male and ovariectomized (Ovx) female rats receiving chronic testosterone and imipramine treatments. Their anxiety and depression-like behaviors were examined using the light-dark box, elevated plus maze, open field, sucrose preference and novelty induced hypophagia tests. RESULTS: In socially isolated rats, the anxiolytic and antidepressant effects of testosterone and imipramine were limited to male rats. Additionally, testosterone enhanced the neurogenic effect of imipramine on hippocampal cell proliferation in male rats. Although female rats exhibited signs of anxiety and depressive-like behaviors following social isolation, testosterone and/or imipramine administration had no anxiolytic or antidepressant effects in Ovx females. CONCLUSIONS: Testosterone and imipramine had anxiolytic and antidepressant effects in socially isolated male, but not female rats. Testosterone enhanced the effect of imipramine on cell proliferation in the hippocampus of male rats.